Integration of Islamic perspectives into medical imaging curriculum: an outcome based education approach - Zainuddin, Zainul Ibrahim (IIUM Press, International Islamic University Malaysia, 2018)
This paper presents a conceptual approach to the integration of Islamic perspectives into a Medical Imaging Curriculum to the concept of Outcome-Based Education (OBE). This work is seen within the context of harmonising Islamic principles to a currently accepted concept in education. Although there have been discussions that question the concept of OBE, this paper contends that the integration can benefit from the practicality aspect of OBE. This can reduce the complexities and fatigue in addressing the integration using an educational approach that is different to that being applied to the human sciences. This paper features the main elements in OBE in the form of Islamic programme educational objectives, Islamic programme outcomes, and Islamic domain learning outcomes. The justification to use domain learning outcomes instead of course learning outcome is given. The teaching and learning strategies, as well as the assessment, are examined through a lens that serves to provide a desirable, practical and holistic model of Islamic integration. It is felt that the currently accepted teaching and assessment methodologies can be adapted for the integration exercise. This work also highlights two often overlooked elements of OBE; teacher and student characteristics. The various terminologies that describe the Islamic teacher characteristics and the differences in student learning styles and preferences are presented. Furthermore, suggestions are made to align the assessment of the integration to various taxonomies of learning, with the aim in evaluating the internalisation of the Islamic essences. This work contents that a holistic approach towards integration of Islamic perspectives into Medical Imaging curriculum can be realised